Legitimation mechanisms in the bailout discourse - Doudaki, Vaia (My University, 2015)
This study examines how the discursive struggles over the constituents of the financial crisis in Greece are policed by mainstream domestic media, in favour of the hegemonic interpretations of the crisis. The study focuses in particular on the discursive mechanisms the Greek press employed to legitimate the bailout agreements Greece signed with the troika. The analysis points to the discursive mechanisms of naturalisation and objectivation that empower the reconstruction of the hegemonic neoliberal rhetoric. The media studied actively participate in the discursive struggle over the crisis, exercising political agency by legitimating the bailout policies as the single course of action for the financial recovery of the country, while selectively omitting or discrediting alternative voices and interpretations.
Keywords: Legitimation; Hegemony; Discourse; Discursive struggles; News; Financial crisis; Bailout; Greece